SR Proteins and Pre-mRNA Splicing in ABA Signaling and Metabolism - Albuquerque-Martins, Rui (2022)
"Plants evolved to reshape their development when adverse growth conditions are perceived. Abscisic acid (ABA) is a major stress phytohormone which rapidly accumulates in plant cells to confer tolerance to abiotic factors that cause osmotic stress, such as drought, high salinity or extreme temperatures. On the other hand, alternative splicing, which allows a single gene to produce multiple transcripts and potentially different protein isoforms, is a key posttranscriptional regulation mechanism in eukaryotic genomes and a potent generator of functional diversity. A tight connection between alternative splicing and plant stress responses has emerged, with stress markedly affecting global splicing patterns and alternative splicing regulating the function of many stress-responsive genes.(...)"